Creative Citizenship – two journeys, one destination - Hargreaves, I.; Hartley, John (Cultural Science, 2015)
This paper is a representation of a live, audio-visual keynote address given at the Creative Citizens Conference in London (September 2014), co-presented by Hargreaves (IH) and Hartley (JH). It seeks to combine (i) autobiographical narrative storytelling – two of them, in fact; with (ii) an attempt to build concepts, themes and strategies out of that narrative, and how the two stories did indeed arrive at ‘one destination’; and (iii) plentiful use of visual prompts, combined with part-scripted, part-improvised dialogic commentary. This approach was risky on the day; it is even harder to render into two dimensions, not least because a vital element, the audience, cannot be represented in that format. Nevertheless, we offer the ‘paper’ as a record of how two intersecting lives and careers were both drawn to the ‘Creative Citizens’ idea, not only as a research problem but also as a component of the speakers’ own practice – one as a high profile journalist turned academic; the other as an academic with interests in alternative models of journalism. We think that our bio-trajectories are relevant to the way that the research project led by Hargreaves has been tackled.